2002
DOI: 10.1111/j.1751-3928.2002.tb00142.x
|View full text |Cite
|
Sign up to set email alerts
|

Victoria Carbonate‐Base Metal Gold Deposit and Its Significance in the Mankayan Mineral District, Luzon, Philippines

Abstract: Abstract:The Victoria gold deposit is a low-sulfidation style epithermal carbonate-base metal gold deposit discovered in 1995 in the Mankayan mineral district, northern Luzon, Philippines. It occurs just south of a high-sulfidation copper-gold orebody (Lepanto enargite deposit) and a porphyry copper-gold orebody (Far Southeast (FSE) deposit). Radiometric dating of the Victoria mineralization yields ages from 1.6 to 1.1 Ma, similar to ages of the Lepanto enargite deposit. Mineralogical, geochemical, fluid inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Similarly, Arribas et al (1995) reported contemporaneous formation of the Lepanto-FSE porphyry Cu-Au deposit and the Lepanto high-sulfidation epithermal Cu-Au deposit (Garcia, 1991;Imai, 1999) at Mankayan district. In addition, the age of the Victoria low-sulfidation epithermal Au deposit (Claveria, 2001;Sajona et al, 2002) was also considered to be contemporaneous with Lepanto-FSE porphyry CuAu deposit and the Lepanto high-sulfidation epithermal Cu-Au deposit (Sajona et al, 2002).…”
Section: Overprinting Hydrothermal Systemsmentioning
confidence: 99%
“…Similarly, Arribas et al (1995) reported contemporaneous formation of the Lepanto-FSE porphyry Cu-Au deposit and the Lepanto high-sulfidation epithermal Cu-Au deposit (Garcia, 1991;Imai, 1999) at Mankayan district. In addition, the age of the Victoria low-sulfidation epithermal Au deposit (Claveria, 2001;Sajona et al, 2002) was also considered to be contemporaneous with Lepanto-FSE porphyry CuAu deposit and the Lepanto high-sulfidation epithermal Cu-Au deposit (Sajona et al, 2002).…”
Section: Overprinting Hydrothermal Systemsmentioning
confidence: 99%
“…5B). The polarity of subduction (west or east dipping) for the older arc is unknown, but it may be a northern extension of the Daguma Arc, which forms the older basement for the Cotabato Arc (appendix A) in Mindanao (Pubellier and others, 1991;Sajona andothers, 1997, 2000). The younger arc overprints the older arc and is also related to east-dipping subduction at the Negros Trench ( fig.…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Postcollisional volcanic rocks vary from calc-alkalic (2.3-0.6 Ma) to shoshonitic (0.5-0.4 Ma) to calc-alkalic (0.3 to the present). The geochemistry of these rocks (OIB 7 -like enrichments in niobium (Nb), high La/Nb ratios) include typical arc as well as adakite-like compositions and may reflect contributions of upwelled mantle (Sajona andothers, 1997, 2000), possibly related to sinking of a detached slab of the Molucca Sea Plate 8 . Any porphyry systems are likely to be related to the pre-collisional rocks.…”
Section: Geologic Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…Most locations are sites of newly discovered deposits or areas of under exploration, except for one abandoned, the Hoshino mine (Belhadi et al, 2002). Hishikari (Imai and Uto, 2002;Sekine et al, 2002;Etoh et al, 2002), Cikidang (Rosana and Matsueda, 2002) and Victoria (Sajona et al, 2002) already became operating mines. Presently exploration activities are being continued in Thorn (Awmack, 2002), Rodnikovoe (Takahashi et al, 2002), Cibaliung (Angeles et al, 2002), Francis Creek (Harijoko et al, 2002) and the north Xinjiang area (Qin et al, 2002), which were noticed in late 1980s to 1990s, and at Nena (Espi et al, 2002).…”
mentioning
confidence: 99%